Manajemen Layanan Bimbingan Konseling Dalam Membentuk Karakter Siswa Di Smp Negeri 3 Burau, Kec. Burau, Kab. Luwu Timur - Nurhayati (Hikamatzu | Journal of Multidisciplinary, 2024)
This thesis discusses the Management of Guidance and Counseling Services in Shaping Student Character at SMP Negeri 3 Burau, sub-district. Burau, district. East Luwu. This research aims to determine the existence of counseling guidance services in shaping student character at SMP Negeri 3 Burau, to find out the management of counseling guidance services in shaping student character at SMP Negeri 3 Burau. The type of research used is descriptive qualitative research. The research subjects are school principals, counselors, students. Data was obtained from observation, interviews and documentation. The results of this research show that: The existence of guidance and counseling services at SMP Negeri 3 Burau really shows its existence through the implementation of various programs which cannot be separated from the implemented school policies, such as orientation services, information services, placement and distribution services, learning services, individual group guidance services. The management of counseling guidance services carried out by counselors in forming character at SMP Negeri 3 Burau goes through several stages including planning counseling guidance in forming student character, organizing counseling guidance in forming student character, implementing counseling guidance in forming student character and organizing counseling guidance in forming character student